2001
DOI: 10.1002/1097-0142(20010115)91:2<333::aid-cncr1006>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of cyclooxygenase-2 in human pancreatic neoplasms and potential for chemoprevention by cyclooxygenase inhibitors

Abstract: BACKGROUND Cyclooxygenase‐2 (COX‐2) is thought to be linked to carcinogenesis; however, very little is known about its expression in pancreatic neoplasms. The authors studied the expression of COX‐2 in human pancreatic neoplasms and investigated the effect of COX inhibitors on the growth of human pancreatic carcinoma cells. METHODS Expression of COX‐2 protein was immunohistochemically examined in 42 human pancreatic duct cell carcinomas (PDCs) and in 29 intraductal papillary mucinous tumors (IPMTs [adenomas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
84
1
7

Year Published

2002
2002
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(95 citation statements)
references
References 34 publications
3
84
1
7
Order By: Relevance
“…There is convincing evidence that NSAIDs, which are inhibitors of cyclooxygenase activity, lower the risk of developing carcinoma of the colon, 6,35,36 esophagus, 9,11,37 and stomach. 10,38 Although the potential therapeutic efficacy of NSAIDs was related exclusively to tumors located in the digestive tract, some studies have suggested that COX-2 may be the target for the prevention and treatment of other carcinomas, including those of the prostate, 8,39 breast, 13,40,41 pancreas, 12,42 head and neck, 43 and the urinary bladder. 44,45 To our knowledge, no epidemiologic studies have been performed to determine the protective effects of COX-2 inhibitors on the development and progression of pituitary tumors.…”
Section: Discussionmentioning
confidence: 99%
“…There is convincing evidence that NSAIDs, which are inhibitors of cyclooxygenase activity, lower the risk of developing carcinoma of the colon, 6,35,36 esophagus, 9,11,37 and stomach. 10,38 Although the potential therapeutic efficacy of NSAIDs was related exclusively to tumors located in the digestive tract, some studies have suggested that COX-2 may be the target for the prevention and treatment of other carcinomas, including those of the prostate, 8,39 breast, 13,40,41 pancreas, 12,42 head and neck, 43 and the urinary bladder. 44,45 To our knowledge, no epidemiologic studies have been performed to determine the protective effects of COX-2 inhibitors on the development and progression of pituitary tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] Increased expression of COX-2 has also been observed in pancreatic cancer, irrespective of histological type and grade, but the mechanisms that control the constitutive and induced expression of COX-2 in human pancreatic carcinoma cells are not completely understood. [12][13][14][15][16][17] The transcriptional activation of COX-2 is mediated by the binding of transcription factors to regulatory elements in the COX-2 promoters, such as nuclear factor κB (NF-κB), CCAAT/enhancerbinding protein (C/EBP), cyclic AMP response element-binding protein (CREB) and nuclear factor-activated T-cell/AP-1, which are involved in COX-2 induction in response to a variety of stimuli in different species and cell types. [18][19][20][21][22][23] For example, the C/EBP family of transcription factors plays an important role in COX-2 induction by lipopolysaccharide and phorbol ester in human vascular endothelial cells, 18 by tumor necrosis factor-α in murine MC3T3-E1 osteoblastic cells, 19 and in mouse skin carcinoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown previously that there is a difference with regard to anatomic localization of melanoma according to patient age; melanomas occurring before the age of 50 years are located preferentially to usually intermittently exposed body sites, whereas melanomas occurring after the age of 50 years are located preferentially to chronically exposed body sites. 5 Hence, thin melanomas, occurring on usually nonexposed body sites in patients age Ͻ 50 years, can be related to intermittent sun exposure, whereas on the contrary, thick melanomas, occurring on exposed body sites in older patients, can be related to chronic sun exposure. The observed decrease in the mean tumor thickness with time could result from an increase in the number of melanomas occurring due to intermittent sun exposure.…”
mentioning
confidence: 99%
“…Cyclooxygenase-2 expression in primary human pancreatic tumors, and the potential role of Cox-2 inhibitors in the management of these tumors, had been previously investigated and reported in four well done studies. [1][2][3][4] It is therefore rather surprising that none of those reports are referenced in the recently published study by Kokawa et al 5 despite a submission occurring after those reports.…”
mentioning
confidence: 99%